Acquired diaphragmatic hernia in a preterm low birth weight neonate. (October 2019) - Captain, Mustafa; Natu, Sanjay; Parekh, Anjali; Naik, A; Behera, MK
Iatrogenic diaphragmatic hernia is rare in children and we report a preterm low birth weight neonate with a presumably acquired diaphragmatic hernia due to trauma caused by treatment following pneumothorax.